Semi-automated title-abstract screening using natural language processing and machine learning - Pilz, Maximilian; Zimmermann, Samuel; Friedrichs, Juliane; Wördehoff, Enrica; Ronellenfitsch, Ulrich; Kieser, Meinhard; Vey, Johannes (Systematic Reviews, 2024)
Title-abstract screening in the preparation of a systematic review is a time-consuming task. Modern techniques of natural language processing and machine learning might allow partly automatization of title-abstract screening. In particular, clear guidance on how to proceed with these techniques in practice is of high relevance
Gesehen am 15.04.2025